A Novel In Vitro Platform Development in the Lab for Modeling Blast Injury to Microglia - Xu, Dasen; Zhang, Nu; Wang, Sijie; Yu, Yawei; Zhang, Pan; Li, Yulong; Yang, Hui (Frontiers in Bioengineering and Biotechnology, 2022)
Traumatic brain injury (TBI), which is mainly caused by impact, often results in chronic neurological abnormalities. Since the pathological changes in vivo during primary biomechanical injury are quite complicated, the in-depth understanding of the pathophysiology and mechanism of TBI depends on the establishment of an effective experimental in vitro model. Usually, bomb explosive blast was employed to establish the in vitro model, while the process is complex and unsuitable in lab. Basing on Water-Hammer, we have developed a device system to provide a single dynamic compression stress on living cells. Series of amplitude (~5.3 MPa, ~9.8 MPa, ~13.5 MPa) were generated to explore the effects of dynamic compression loading on primary microglia within 48 h. Apoptosis experiments indicated that primary microglia had strong tolerance to blast waves. What’s more, the generation of intercellular reactive oxygen species and secretory nitric oxide were getting strongly enhanced and recovered within 48 h. In addition, there is a notable release of pro-inflammatory cytokine by microglia. Our work provides a reproducible and peaceable method of loading single dynamic compression forces to cells in vitro. Microglia did have an acute inflammatory response to dynamic loadings, while no significant cell death was observed. This insight delivers a new technological approach that could open new areas to a better understanding of the mechanism of cell blast injuries.